2020
DOI: 10.1177/1120700020904337
|View full text |Cite
|
Sign up to set email alerts
|

Weak psoas and spine extensors potentially predispose to hip fracture

Abstract: Introduction: We performed a computed tomography analysis of muscle composition characteristics in hip fracture patients and non-hip fracture controls. Methods: In total, 43 patients (9 men, 34 women) were included in the hip fracture group, matched 1 to 1 with non-hip fracture controls. Muscle cross-sectional areas were measured in axial CT scan at the body level of the 4th lumbar vertebra (L4), intervertebral disc level between the 5th lumbar vertebra and the 1st sacral vertebra (L5-S1) and just below level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…Another established fall factor that should be corrected is a decline in muscle quality in certain areas. The fall risk is related to the mass of the psoas major muscle and the extensor muscle of the spine, and weak psoas and spine extensors may increase the risk of fracture ( 78 ). In addition, a cohort study involving 7,575 women aged 75 or older showed that neuromuscular injury (gait speed and tandem walk) and poor vision were important and independent predictors of hip fracture risk ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another established fall factor that should be corrected is a decline in muscle quality in certain areas. The fall risk is related to the mass of the psoas major muscle and the extensor muscle of the spine, and weak psoas and spine extensors may increase the risk of fracture ( 78 ). In addition, a cohort study involving 7,575 women aged 75 or older showed that neuromuscular injury (gait speed and tandem walk) and poor vision were important and independent predictors of hip fracture risk ( 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Higher fat mass could also increase bone strength through increased mechanical loading and enhanced oestrogen production [ 38 ]. Low muscle mass and strength of the hip flexor muscles and spine extensors have also been associated with an increased risk of hip fracture [ 40 ], possibly due to reduced balance and mobility. Weight management may therefore be an important consideration in reducing hip fracture risk in vegetarians, but further research is required to explore the roles of BMI and body composition in hip fracture risk in vegetarians and meat-eaters.…”
Section: Discussionmentioning
confidence: 99%
“…As a joint adverse event of imbalance, falling is also a well-known factor in fractures among older adults. 30 Kim et al 31 suggested that a weak PM should be used as a significant predictor of falls and hip fractures in osteoporotic patients. Statistically, falling accounts for 87% of all types of fractures in the elderly, and these fractures are virtually always due to low-impact injuries in osteoporotic bones.…”
Section: Discussionmentioning
confidence: 99%